A note on Dodgson’s Rock platform, Elkington quarry, and the origin of bornhardts on north-western Eyre Peninsula, South Australia (Cadernos do Laboratorio Xeolóxico de Laxe. Revista de Xeoloxía Galega e do Hercínico Peninsular, 2024)
The excavation of what was Dodgson‘s Rock, now Elkington quarry, exposed a domical bedrock form that can be construed as a stage in the development of incipient bornhardts. It confirmed the earlier interpretation of the domical inselberg known as Ucontitchie Hill as a structural feature initiated by the differential etching in the shallow subsurface of compartments of granitic rock of contrasted fracture density and exposed by the erosional lowering of the densely fractured and weathered surrounds. Stages in the excavation provided evidence concerning the nature of sheet fractures and structures as well as the origin of breached arches or A-tents. Other bornhardts in the district (Mt Wudinna, Polda Rock, Little Wudinna Hill) as well as sundry additional inselbergs, turrets, and elevated platforms may be of a similar origin.